Design and Analysis of Randomized Controlled Trials and Observational Studies, with a Focus on Addressing Sources of Bias, Confounding, and Heterogeneity in Kenya - Otieno, Jackson (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to investigate design and analysis of randomized controlled trials and observational studies, with a focus on addressing sources of bias, confounding, and heterogeneity Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Kenya, it is vital to address bias, confounding, and heterogeneity in randomized controlled trials and observational studies. Robust methodologies, including randomization and propensity score matching, are utilized to enhance validity. Consideration of local contextual factors, such as cultural norms and healthcare infrastructure, is crucial. Collaboration among researchers, policymakers, and communities is key to ensuring the quality and relevance of research for improving health outcomes in Kenya. Unique Contribution to Theory, Practice and Policy: Randomization theory, causal inference theory & heterogeneity theory may be used to anchor future studies on design and analysis of randomized controlled trials and observational studies, with a focus on addressing sources of bias, confounding, and heterogeneity. Rigorous research methods improve the quality of evidence available to practitioners, helping them make informed decisions. High-quality research informs evidence-based policymaking.